تلقي القران الكريم بأجازة أسانيد القراءات في المراكز القرآنية المختارة بماليز يا : العوائق والمساهمات - Norazman Alias (Universiti Sains Islam Malaysia, 2024)
This study is focusing on the learning of talaqqi al-quran phenomenon which is gaining a place among the societies.Based on the researcher’s observation,there are several Quranic learning centres that offer talaqqi al-quran programs such as Sultan Ismail Petra International Islamic College,Kelantan,Al-Mufid Studies Center,Terengganu and Ainihafeez Enterprise,Selangor.However,these institutions appear to encounter various hurdles and obstacles in conducting the program.Therefore,the present study is an endeavour to investigate the obstacles encountered by them and to analyse the contributions of each institution in talaqqi al-quran program.The study is qualitative in nature in which textual analysis would be employed as a main instrument to examine the concept of talaqqi al-quran.Selected sanad of al-quran were scrutinized to understand the nature of its authenticity.In study will use quantitative methodology to examine how effective the talaqqi al-quran program has attracted the public to participate in the program.The study in its findings indicate that the interest of the society from various ages has increased towards talaqqi al-quran program even though in a small number of participants.Howeever,the researcher found that there are several obstacles that the organizers have to overcome in such programs such as enhancing the teaching and learning modules,program management and the number of teachers involved.